Political risk and success factors in public-private partnerships at the subnational level: the case of road infrastructure concessions - Mestizo Reyes, Rubén D. (Pontificia Universidad Católica del Perú, 2018)
Public-Private Partnerships (PPP) are contractual figures through which the public and private sectors participate together in the provision of public goods and services, with multiple degrees of involvement and allocation of responsibilities, and multiple types of arrangements such as concessions (PPP in Infrastructure Resource Center [PPPIRC], 2015). Thus, an adequate risk distribution among the parties is required to ensure the success of a project. Although there is extensive research to understand risk in PPP at the national level, it has been found that there is a lack of research on the role of political risk and critical success factors coming from subnational spheres, on PPP success. Therefore, the current study related perceptions on political risk, and critical success factors with the probability of success or failure of an infrastructure project performed under concessions at the subnational level. The types of political risk included were: (a) currency inconvertibility, (b) breach of contract, (c) expropriation, (d) political violence, (e) legal and bureaucratic risk, and (f) non-governmental actions. Meanwhile, the critical success factors involved were: (a) favourable economic conditions, (b) available financial markets, (c) effective procurement and (d) government guarantee (Hardcastle et al., 2005). These factors were related through structural equation modelling (SEM). Results showed that both critical success factors and political risk factors were found to have a significant relationship with the success or failure of PPP in infrastructure projects at the subnational levels. There was a statistically significant, positive relationship, between critical success factors and success of public-private partnership infrastructure projects. Furthermore, there was a statistically significant, positive, indirect effect of political risk factors on success, following the idea that properly identified critical success factors and political success factors influence the final outcome of a project at the subnational level. In turn, political risk factors had a statistically significant effect on critical success factors, thus proving the relationship between both constructs found in the literature. These results confirmed the importance of both political risk and critical success factors on PPP success or failure, as well as remarking the need of taking subnational factors into account when dealing with such projects.
Keywords: Comportamiento organizacional; Aprendizaje organizacional; Concesiones--Carreteras; Investigación cuantitativa; https://purl.org/pe-repo/ocde/ford#5.02.04